Evaluación Del Programa “Somos Reconocimiento” Frente Al Salario Emocional En La Organización Sodexo (2019)
The purpose of this project was to evaluate the “we are recognition” program of the Sodexo Company in order to identify the importance and application of emotional salary within the program. It was oriented to the different areas of the company, where information was collected corresponding to the perspective of the area in charge of implementation; Through a qualitative research framework, the collection of information was carried out through two instruments such as the survey and the semi-structured interview, with questions related to the different categories established and then evaluated